2009
DOI: 10.1097/nnr.0b013e3181ac142a
|View full text |Cite
|
Sign up to set email alerts
|

A New Self-Report Measure of Self-Management of Type 1 Diabetes for Adolescents

Abstract: Background The development of instruments to measure self-management in youth with type 1 diabetes has not kept up with current understanding of the concept. Objective To report the development and testing of a new self-report measure to assess self-management of type 1 diabetes in adolescence (SMOD-A). Methods Following a qualitative study, items were identified and reviewed by experts for content validity. A total of 515 adolescents, 13 to 21 years old, participated in a field study by completing the SMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
119
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 27 publications
2
119
1
Order By: Relevance
“…18 Past researchers using the SMOD-A have reported acceptable internal consistency reliabilities ranging from .71 to .85 across subscales. 19 Test-retest reliability was adequate at 2 weeks ( r = .60 to .88) and at 3 months ( r = .59 to .85). Construct validity has also been established with the Diabetes Quality of Life for Youth Questionnaire, Self-Efficacy for Diabetes Scale, A1C, Diabetes Self-Management Profile, and Self-Care Inventory.…”
Section: Methodsmentioning
confidence: 92%
“…18 Past researchers using the SMOD-A have reported acceptable internal consistency reliabilities ranging from .71 to .85 across subscales. 19 Test-retest reliability was adequate at 2 weeks ( r = .60 to .88) and at 3 months ( r = .59 to .85). Construct validity has also been established with the Diabetes Quality of Life for Youth Questionnaire, Self-Efficacy for Diabetes Scale, A1C, Diabetes Self-Management Profile, and Self-Care Inventory.…”
Section: Methodsmentioning
confidence: 92%
“…Higher scores suggest parents have greater self-efficacy regarding their ability to care for their child’s T1D. Previous studies have found good internal consistency (α = .90), reliability, and construct validity estimates (Armstrong, Mackey, & Streisand, 2011; Grossman et al, 1987; Schilling et al, 2009; Streisand et al, 2005). In the current sample, the SED-P had an acceptable Cronbach’s alpha of .78.…”
Section: Methodsmentioning
confidence: 95%
“…12 Adolescents 13 years and older also completed the Self-Management of Type 1 Diabetes for Adolescents (SMOD-A) questionnaire. 13 Data regarding the presence and care of a household pet were obtained at baseline and at the three month follow-up visit. Demographics and duration of T1DM were assessed for all participants.…”
Section: Methodsmentioning
confidence: 99%